CT Attenuation and Cross-Sectional Area of the Pectoralis Are Associated With Clinical Characteristics in Chronic Obstructive Pulmonary Disease Patients - Qiao, Xin; Hou, Gang; Kang, Jian; Wang, Qiu-Yue; Yin, Yan (Frontiers in Physiology, 2022)
Purpose: Muscle wasting is associated with prognosis in patients with chronic obstructive pulmonary disease (COPD).Computed tomography (CT) could serve as a method for muscle assessment due to its ability to measure both muscle quantity (e.g., cross-sectional muscle area) and muscle quality (e.g., muscle attenuation). Our study aimed to compare the differences in CT-derived pectoralis muscle cross-sectional area (PMA) and pectoralis muscle attenuation (PMT) between COPD patients and healthy controls and explore the association between PMA and PMT measurements and clinical characteristics in patients with COPD. Methods: A total of 252 participants included in our analysis consisted of 80 healthy controls and 172 patients with COPD. PMA and PMT were measured from a single axial slice of the CT scan above the aortic arch. The linear regression analysis was used for determining the correlation between PMA and PMT measurements and clinical characteristics in patients with COPD. Associations were adjusted for age, sex, BMI, FEV1%pred, smoking packyears, current smoking status, emphysema percentage, and total airway count (TAC) of the right upper lobe apical bronchus (RB1). Results: PMA and PMT were lower in COPD patients, especially those with acute exacerbation, than in healthy controls. PMA and PMT were significantly associated with the severity of emphysema and the TAC of RB1(P < 0.05). Patients with stable COPD who had lower PMA and lower PMT had significantly worse pulmonary function, poorer exercise tolerance, decreased quality of life, and worse dyspnea scores. In addition, patients with acute COPD exacerbation who had lower PMA and lower PMT had a higher risk of respiratory failure on admission. Conclusion: CT-derived measurements of the pectoralis muscle may be helpful to detect declines in muscle quantity and quality and predict disease severity in patients with COPD.